2014
DOI: 10.3892/or.2014.3290
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CXCR7 inhibits proliferation and invasion of osteosarcoma cells through inhibition of the PI3K/Akt and β-arrestin pathways

Abstract: Abstract. CXC chemokine receptor 7 (CXCR7) has been implicated in tumor development and metastasis in multiple malignancies. Yet, the function and molecular mechanisms of CXCR7 in human osteosarcoma (OS) are still unclear. The aim of the present study was to investigate the role of CXCR7 in human OS. The expression of CXCR7 was assessed by immunohistochemical assay using a tissue microarray procedure in 45 cases of OS tissues. A loss-of-function approach was used to observe the effects of lentiviral vector-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Regarding the biological functions of CXCL12 and CXCR7 in cells, existing reports have focused on cell proliferation 47 , invasion 48 and migration 49 . To date, the role of CXCR7 in regulating angiogenesis in HUVECs has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the biological functions of CXCL12 and CXCR7 in cells, existing reports have focused on cell proliferation 47 , invasion 48 and migration 49 . To date, the role of CXCR7 in regulating angiogenesis in HUVECs has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…. Evidence shows that the PI3K/Akt signaling pathway is closely correlated with cancer cell biology, including OS (34,35). In addition, Lu et al (36) showed that ARHI inhibits the PI3K/Akt signaling pathway in ovarian cancer cells.…”
Section: Overexpression Of Arhi Is Directly Associated With the Inhibmentioning
confidence: 99%
“…The critical role of CXCR7 in mediating OS progression in the lungs and its lung metastasis-enhancing effect on OS expressing CXCR4 has been reported ( 42 , 43 ). CXCR7 is also found to be involved in OS proliferation ( 44 ).…”
Section: Introductionmentioning
confidence: 99%